Variations in food and feeding habits of Megalops cyprinoides fr~ coastal waters of Visakhapatnam - Rao, L M; Padmaja, G (Indian Journal of Fisheries, 2011)
The food and feeding habits of Megalops cyprinoides from the polluted waters ofVisakhapatnam harbour in comparison with the unpolluted waters of Yerragedda.mouth have been investigated. There are marked differences in the food habitsof the fish inhetween the two habitats. Prawns formed the main food item atthe polluted Visakhapatnam -harbour-while aquatic insects dominated the gutcontents at the unpolluted Yerragedda mouth. The reasons for the variation infood and feeding habits have been discussed in detail.